1987
DOI: 10.1152/ajpcell.1987.252.6.c595
|View full text |Cite
|
Sign up to set email alerts
|

Role of sodium-calcium exchange in regulation of intracellular calcium in nerve terminals

Abstract: Ca efflux from rat brain presynaptic nerve terminals (synaptosomes) was examined after loading the terminals with 45Ca during a brief depolarization, usually in media containing 20 microM Ca labeled with 45Ca, to assure a small (physiological) load. Efflux of 45Ca was very slow in the absence of external Na and Ca (approximately 0.5% of the load/s) and was greatly accelerated by Na and/or Ca (presumably Na+-Ca2+ and Ca2+-Ca2+ exchange, respectively). The dependence of 45Ca efflux on external Na was sigmoid, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(50 citation statements)
references
References 28 publications
5
45
0
Order By: Relevance
“…In neuronal compartments with a high surface-to-volume ratio, CCMs in the plasma membrane may clear cytosolic Ca 2ϩ more efficiently than other CCMs that sequestrate Ca 2ϩ into intracellular organelles. Various axon terminals effectively clear Ca 2ϩ using plasma membrane CCMs such as Na/CaX and PMCA (Gill et al, 1981;Sanchez-Armass and Blaustein, 1987;Reuter et al, 1995;Morgans et al, 1998;Zenisek et al, 2000;Chuhma and Ohmori, 2002;Lee et al, 2002). Our results indicate that Na/CaX is a primary CCM at the calyx of Held.…”
Section: Role Of Na/cax In the Calyx Of Heldmentioning
confidence: 52%
“…In neuronal compartments with a high surface-to-volume ratio, CCMs in the plasma membrane may clear cytosolic Ca 2ϩ more efficiently than other CCMs that sequestrate Ca 2ϩ into intracellular organelles. Various axon terminals effectively clear Ca 2ϩ using plasma membrane CCMs such as Na/CaX and PMCA (Gill et al, 1981;Sanchez-Armass and Blaustein, 1987;Reuter et al, 1995;Morgans et al, 1998;Zenisek et al, 2000;Chuhma and Ohmori, 2002;Lee et al, 2002). Our results indicate that Na/CaX is a primary CCM at the calyx of Held.…”
Section: Role Of Na/cax In the Calyx Of Heldmentioning
confidence: 52%
“…To clarify whether NCX is effectively involved in A1254-induced [Ca 2ϩ ] i increase, the pattern of the expression of the three known NCX isoforms NCX1, NCX2 and NCX3 was first characterized in SH-SY5Y cells by RT-PCR analy- Inglefield and Shafer (2000), with a consequent opening of Na ϩ -sensitive voltage channels. This event leads to an increase of intracellular Na ϩ ion concentration, which in turn may force the NCX to work in the reverse mode (Baker and McNaughton, 1976;DiPolo, 1979;Sanchez-Armass and Blaustein, 1987;Annunziato et al, 2004). This chain of events seems to be supported by the results showing that tetrodotoxin, a well known blocker of fast-activated Na ϩ channels (Almers and Levinson, 1975;Weiser and Wilson, 2002), prevents Ca 2ϩ oscillations evoked by A1254 in developing cortical neurons (Inglefield and Shafer, 2000).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, it has been reported that PCBs can also perturb Ca 2ϩ homeostasis by acting on ryanodine (Wong and Pessah, 1996;Mundy et al, 1999) and inositol 1,4,5-triphosphate receptorsensitive Ca 2ϩ release (Inglefield et al, 2001). The Na ϩ -Ca 2ϩ exchanger (NCX) is a plasmamembrane exchanger mainly involved in the maintenance of cytosolic Ca 2ϩ homeostasis (Sanchez-Armass and Blaustein, 1987). This antiporter couples the uphill extrusion of Ca 2ϩ to the entrance of Na ϩ into the cell (forward mode) and down its electrochemical gradient.…”
mentioning
confidence: 99%
“…Complex patterns regulate the specificity of Ca 2ϩ signaling through the activity of plasma membrane channels and transporters, including the Na ϩ /Ca 2ϩ exchanger (NCX). For instance, this bidirectional high-capacity and low-affinity ionic transporter, by exchanging three Na ϩ ions for one Ca 2ϩ ion (Sanchez-Armass and Blaustein, 1987;Annunziato et al, 2004), plays a relevant role in maintaining intracellular free Ca 2ϩ homeostasis. Three different gene products of NCX have been cloned (Nicoll et al, 1990(Nicoll et al, , 1996Li et al, 1994): NCX1, which is the only isoform expressed in the heart and is ubiquitously expressed in several tissues, and NCX2 and NCX3, which are widely expressed in the brain (Papa et al, 2003) and in the skeletal muscle (Lee et al, 1994).…”
Section: Introductionmentioning
confidence: 99%